Информационная система массового доступа по радиотрансляционной сети - Семенец, В. В.; Татарчук, С. И.; Курицын, В. Н.; Осипов, Ю. Б.; Подпружников, П. М.; Радченко, В. И. (УАДО, 2002)
The brief historical help is reduced. The structure of threelinks network of wire broadcasting is reviewed and the brief characteristic of the radiotransmitting network is reduced The problem of wire broadcasting network possibility as physical area for data transfer is elucidated. The practical implementation results of project of a bidirectional TF channels on WB networks and also the full access to a global network internet by the transmitting point are reduced
Keywords: радиотрансляционная сеть; образование